Ramayana Cikarang : Antara Kepercayaan Lokal, Rezeki, Dan Resiliensi Pedagang - M. Alpariji; Noor Azida Batubara; Nur Azizah Zakiah; Amaliyah Sabila Rosyadah; Zumrotussa’adah; Ayu Ardelia (JURNAL ILMIAH NUSANTARA, 2026)
The phenomenon of the strong mental resilience among traders at Ramayana Cikarang reflects a tangible form of psychological endurance and spiritual strength amid a challenging environment. Despite the building’s deteriorating condition, frequent fires, and recurring stories of supernatural disturbances, many traders continue to remain in the same location. Their decision is influenced by economic factors, customer loyalty, and a religious conviction that sustenance (rezeki) is predetermined by Allah SWT. Using the perspective of the psychology of religion, this article explores how religiosity and spiritual beliefs shape the traders’ mental resilience in facing uncertainty and risk. The findings indicate that faith and spiritual meaning serve as primary sources of peace, hope, and courage in confronting difficult situations.